Performing at the Top of One's Musical Game - Hatfield, Johannes L. (Frontiers in Psychology, 2016)
The purpose of the present mixed method study was to investigate personal benefits, perceptions, and the effect of a 15-week sport psychological skills training program adapted for musicians. The program was individually tailored for six music performance students with the objective of facilitating the participants’ instrumental practice and performance. The participants learnt techniques such as goal setting, attentional focus, arousal regulation, imagery and acceptance training/self-talk. Zimmerman’s (1989) cyclical model of self-regulated learning was applied as a theoretical frame for the intervention. The present study’s mixed-method approach (i.e., quan+ QUAL) included effect size, semi-structured interviews, a research log, and practice diaries of the participants (Creswell, 2009). Thematic analysis revealed that participants had little or no experience concerning planning and goal setting in regard to instrumental practice. Concentration, volition, and physical pain were additional issues that the participants struggled with at the time of pre-intervention. The study found that psychological skills training (with special emphasis on planning and goal setting) facilitated cyclical self-regulated learning patterns in the participants. In essence, the intervention was found to facilitate the participants’ concentration, self-observation, self-efficacy, and coping in the face of failure. The appliance of practice journals facilitated the participants` self-observation, self-evaluation, and awareness of instrumental practice. Finally, the psychological skills intervention reduced participants’ worry and anxiety in performance situations. An eight-month follow up interview revealed that the participants were still actively applying psychological skills.